2009
DOI: 10.2215/cjn.02790608
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Soluble TWEAK and Inflammation on Mortality in Hemodialysis Patients

Abstract: Background and objectives: Chronic kidney disease (CKD) is characterized by an exceptionally high mortality rate, primarily due to cardiovascular disease. Reduced soluble TNF-like weak inducer of apoptosis (sTWEAK) plasma levels have been reported both in patients with subclinical atherosclerosis and CKD.Design, participants, & measurements: A cross-sectional study was conducted in 218 prevalent patients (121 men; 63 ؎ 14 yr) undergoing hemodialysis (HD). sTWEAK levels in relation with the patients' outcome we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
89
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 35 publications
16
89
4
1
Order By: Relevance
“…Furthermore, because IL-6 induces the production of Fn14, it has been suggested that a persistently inflamed state may exacerbate the action of TWEAK through increased receptor synthesis (29). Thus, as we observed that simultaneously elevated levels of TWEAK and IL-6 in dialysis patients were associated with significant reductions in IGF-1 and handgrip strength, this combination may lead to muscle catabolism (27).…”
Section: Inflammation Exacerbates the Effects Of Protein-energy Wastingmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, because IL-6 induces the production of Fn14, it has been suggested that a persistently inflamed state may exacerbate the action of TWEAK through increased receptor synthesis (29). Thus, as we observed that simultaneously elevated levels of TWEAK and IL-6 in dialysis patients were associated with significant reductions in IGF-1 and handgrip strength, this combination may lead to muscle catabolism (27).…”
Section: Inflammation Exacerbates the Effects Of Protein-energy Wastingmentioning
confidence: 53%
“…They proposed that angiotensin II may stimulate an interaction between the liver and the skeletal muscle because the liver becomes the major source of IL-6 and serum amyloid A. Second, elevated IL-6 and soluble TNF-like weak inducer of apoptosis (TWEAK) levels have additive effects on outcome prognostication ( Figure 2B) (27). TWEAK is a member of the TNF superfamily, which through binding to its receptor Fn14 mediates various biologic effects, including exacerbation of the inflammatory response and muscle-wasting activation through the ubiquitin-proteasome and NF-B pathways (28).…”
Section: Inflammation Exacerbates the Effects Of Protein-energy Wastingmentioning
confidence: 99%
“…Unexpectedly, lower plasma sTWEAK has been reported in subjects with subclinical atherosclerosis, diabetic subjects, CKD patients (18 -20,36), and in this study. In CKD patients, sTWEAK appeared to be robustly and negatively associated with ED (19), and sTWEAK plasma concentrations were good prognosticators of all-cause and CVD mortality in patients undergoing hemodialysis (18). Interestingly, in patients with chronic stable heart failure, reduced sTWEAK levels predicted an adverse prognosis independently of established risk markers such as the N-terminal prohormone of brain natriuretic peptide (37) and contributed to improve the prediction of coronary artery disease (38).…”
Section: Discussionmentioning
confidence: 96%
“…Binding of TWEAK to its receptor, Fn14 (13), mediates multiple biologic effects such as cellular growth, proliferation, and migration; osteoclastogenesis; angiogenesis; and apoptosis (15)(16)(17). sTWEAK plasma levels decrease with impaired renal function and associate with the aggravation of the endothelial function and the mortality risk (18,19). In the same line, diminished sTWEAK levels have been reported in patients with subclinical atherosclerosis (20).…”
mentioning
confidence: 91%
“…The pathophysiological basis of inflammatory cytokines, and particularly of IL-6-induced PEW, may be increased protein catabolism (19,20) and/or resistance to the anabolic effect of growth hormone, which may contribute to the loss of strength and muscle mass (21); in addition, inflammation may affect appetite and eating behavior (22,23). It was recently suggested that interactions between inflammatory markers and sTWEAK (soluble TNF-like weak inducer of apoptosis) affect the nutritional status of prevalent HD patients; thus, significant reductions in markers of PEW (IGF-1 and handgrip strength) associated with high levels of both IL-6 and sTWEAK may provide an additional link between inflammation and PEW (24). The malignant form of PEW, essentially caused by chronic inflammation in the HD population, is associated with pronounced hypoalbuminemia, markedly increased resting energy expenditure, oxidative stress, and poor clinical outcome, and has been termed as "malnutrition type 2" by Stenvinkel et al (25).…”
Section: Introductionmentioning
confidence: 99%